A testing tool for information visualizations based on user interactions - Schiaffino, Martín (2022)
Decision-making has become a vital process in any organization, evolving from a process based on experience and intuition to one increasingly established in data analysis. One type of specialized software for data analysis is that of visual representations for large data sets. Visual representations are critically important today as they enable effective exploration of a data set and facilitate the task of identifying patterns and drawing conclusions. Every day more decisions are made based on visual analysis through visual representations of large data sets. It is not only a quantitative but also a qualitative increase. Decisions are more critical and with more impact on society, the environment, and individuals. In this context, it is essential to develop new and better methodologies and tools that allow the visualization developer to ensure the correct functioning of visual representations and their interactions. To achieve this goal, we present Test Suite Editor, a platform that assists in visualization testing. This platform facilitates the generation of test cases based on user interactions. This contribution is based on a previously published black box testing technique for information visualizations that uses regular expressions to represent the sequence of user interactions.